Challenges to community transitions through Money Follows the Person. (27th January 2020) - Robison, Julie; Shugrue, Noreen; Porter, Martha; Baker, Kristin
Abstract: Objective: To examine the effects of transition challenges on the success and timeliness of transitions from institutions to community living for long‐stay participants in the Money Follows the Person (MFP) Rebalancing Demonstration and determine whether outcomes vary by age and disability. Data Source: Secondary data on transition challenges for individuals enrolled in Connecticut's MFP program between December 2008 and December 2017. Study Design: Challenges were analyzed for older adults, people with mental health disability, and people with physical disability. Bivariate and multivariate analyses investigated which transition challenges and selected demographic variables predict transition versus closure and length of transition period for each group. Data Extraction Methods: The sample includes 3506 persons who attempted transition from institutions to community living and whose case concluded with transition or closure from 2015 to 2017. Principal Findings: The association between most transition challenges and the ability of long‐stay institutional residents to return to the community, and to do so in a timely manner, varies significantly among older adults and younger persons with physical or mental health disabilities. For all groups, however, consumer engagement challenges predicted closure without transition (OR: 1.3‐3.9) and housing challenges predicted longer transition periods (84‐132 days). Length of institutional stay was associated with both outcomes for older adults and persons with physical disability. Other challenges, such as issues with services and supports, differed among the three groups on both outcomes. Conclusions: Knowledge of the effects of transition challenges on success and timeliness of transition for each group allows program managers and health and service providers to focus resources on addressing the most serious challenges. Particular emphasis should be placed on consumer engagement and housing challenges, and on targeting persons for transition early in their institutional stay. Federal and state transition programs can benefit by individualizing supports for residents to yield successful outcomes.